A novel BRCA1 splicing variant detected in an early onset triple-negative breast cancer patient additionally carrying a pathogenic variant in ATM: A case report - Colombo, Mara; Mondini, Patrizia; Minenza, Elisa; Foglia, Claudia; Mosconi, Annamaria; Molica, Carmen; Pistola, Lorenza; Ludovini, Vienna; Radice, Paolo (Frontiers in Oncology, 2023)
The widespread adoption of gene panel testing for cancer predisposition is leading to the identification of an increasing number of individuals with clinically relevant allelic variants in two or more genes. The potential combined effect of these variants on cancer risks is mostly unknown, posing a serious problem for genetic counseling in these individuals and their relatives, in whom the variants may segregate singly or in combination. We report a female patient who developed triple-negative high grade carcinoma in the right breast at the age of 36 years. The patient underwent bilateral mastectomy followed by combined immunotherapy and chemotherapy (IMpassion030 clinical trial). Two years later she developed a skin recurrence on the right anterior chest wall. Despite intensive treatment, the patient died at 40-year-old due to disease progression. Gene panel testing of patient’s DNA revealed the presence of a protein truncating variant in ATM [c.1672G>T; p.(Gly558Ter)] and of a not previously reported variant in the BRCA1 exon 22 donor splice site [c.5406+6T>C], whose clinical significance was unknown. The analysis of patient’s RNA revealed the up-regulation of two alternative BRCA1 mRNA isoforms derived from skipping of exon 22 and of exons 22-23. The corresponding predicted protein products, p.(Asp1778GlyfsTer27) and p.(Asp1778_His1822del) are both expected to affect the BRCA1 C Terminus (BRCT) domain. The two variants were observed to co-occur also in the proband’s brother who, in addition, was heterozygous for a common variant (c.4837A>G) mapped to BRCA1 exon 16. This allowed to ascertain, by transcript-specific amplification, the lack of functional mRNA isoforms expressed by the c.5406+6T>C allele and provided evidence to classify the BRCA1 variant as pathogenic, according to the guidelines of the Evidence-based Network for the Interpretation of Germline Mutant Alleles (ENIGMA) consortium. To our knowledge, excluding two cases detected following the screening of population specific recurrent variants, only one ATM/BRCA1 double heterozygote has been reported in the literature, being the case here described the one with the youngest age at cancer onset. The systematic collection of cases with pathogenic variants in more than one cancer predisposition gene is needed to verify if they deserve ad hoc counseling and clinical management.